Adjuvant rituximab treatment for pemphigus: A retrospective study of 45 patients at a single center with long‐term follow up. Issue 6 (10th February 2017) - Kim, Tae Hyung; Choi, Yuri; Lee, Sang Eun; Lim, Jung Min; Kim, Soo‐Chan
Abstract: To evaluate the long‐term outcomes of rituximab in the treatment of pemphigus and the influence of disease duration and different dose of rituximab on the clinical response, 45 patients with refractory pemphigus treated with at least one cycle of two infusions of rituximab (375 mg/m 2 per infusion weekly) were retrospectively studied. All patients were followed up for more than 2 years. All patients achieved complete or partial remission within 8 months of the first cycle. Thirty‐four (76%) patients relapsed at a median of 17 months. All patients who received additional cycles after relapse achieved new remissions. Early use of rituximab within 1 year of disease duration and high‐dose therapy induced better outcomes, although the results in early use were not statistically significant. Acute respiratory distress syndrome occurred in one patient. Rituximab is effective in treating pemphigus, but relapses are frequent during long‐term follow up, and additional cycles are beneficial in relapsed cases. Early and high‐dose rituximab therapy may be more effective.